Phonetic, semantic, spelling and lexical changes in French - BOUSSEBAT, Omar (Journal of Human Sciences, 2023)
French, as a romance language, has, during its history, been the the subject of several changes that relate of the realization of phonems, to the lexicon, the meaning of words and the spelling. The questions that we are going to raise in this contribution are the following : what are the reasons why the minimum units of the French ? Which ones are behind the semantic changes ? To what is due the evolution of its spelling ? To discover the modifications in which we are interested we call on a corpus which includes words taken from the language dictionary, Le Nouveau Petit Robert, from the work of the linguist, A. BENTOLILA, which is entitled : « Vocabulary », from pantagruel’s letter to his son Gargantua, two characters from F. RABELAIS.